2)3/ 8 ÷ 1 /2 = 3 /8 × 2/ 1 = 3·2 /8·1 = 6/ 8 = 3 · 2/ 4 · 2 = 3/ 4 = 0.75
4)1 /12 ÷ 1/ 6 = 1/ 12 × 6/ 1 = 1·6/ 12·1 = 6 /12 = 1 · 6 /2 · 6 = 1 /2 = 0.5
6)2 /7 ÷ 3 /7 = 2 /7 × 7 /3 = 2·7 /7·3 = 14/ 21 = 2 · 7 /3 · 7 = 2 /3
8)3 /4 ÷ 5 /8 = 3 /4 × 8 /5 = 3·8 /4·5 = 24 /20 = 6 · 4/ 5 · 4 = 6/ 5 = 1·5 + 1 /5 = 1 / 1 5 = 1.2
Пошаговое объяснение: Вроде бы этот учебник)
2)3/ 8 ÷ 1 /2 = 3 /8 × 2/ 1 = 3·2 /8·1 = 6/ 8 = 3 · 2/ 4 · 2 = 3/ 4 = 0.75
4)1 /12 ÷ 1/ 6 = 1/ 12 × 6/ 1 = 1·6/ 12·1 = 6 /12 = 1 · 6 /2 · 6 = 1 /2 = 0.5
6)2 /7 ÷ 3 /7 = 2 /7 × 7 /3 = 2·7 /7·3 = 14/ 21 = 2 · 7 /3 · 7 = 2 /3
8)3 /4 ÷ 5 /8 = 3 /4 × 8 /5 = 3·8 /4·5 = 24 /20 = 6 · 4/ 5 · 4 = 6/ 5 = 1·5 + 1 /5 = 1 / 1 5 = 1.2
Пошаговое объяснение: Вроде бы этот учебник)